Metaheuristics for Intelligent Electrical Networks - Héliodore, édéric; Nakib, Amir; Ismail, Boussaad; Ouchraa, Salma; Schmitt, Laurent (John Wiley & Sons, Incorporated, 2017)
The optimization tools are ubiquitous in modeling and the use of electrical networks. Managing the complexity of these electrical networks leads to analyze and define new methodologies, able to combine performance and near-operational processing. Metaheuristics offer a range of solutions as efficient as they are innovative.